137k views
5 votes
How to simplify -2a+3a+6

User Mck
by
6.1k points

2 Answers

3 votes

Hi there!

Here are all the steps into simplifying this :

Since "-2a" and "3a" share the same variable, which is "a", you can add both coefficients to be left with just one variable instead of two :

-2 + 3 = 1

Since the coefficient of "a" would be 1, you can just write "a", which is the same thing.

So the simplified expression would be : a + 6


There you go! I really hope this helped, if there's anything just let me know! :)

User RileyManda
by
6.1k points
3 votes

Answer:

-2a + 3a +6 = a + 6

Explanation:

Combine Like Terms:

=−2a+3a+6

=(−2a+3a)+(6)

=a+6

User Matthew Benedict
by
6.4k points